Arm-leg coordination in recreational and competitive breaststroke swimmers - Leblanc, H.; Seifert, L.; Chollet, D. (Journal of Science and Medicine in Sport, 2009)
The aims of this study were to assess the durations of the different arm and leg stroke phases (propulsion, glide, and recovery) and the temporal arm-leg gaps between 12 competitive and 12 recreational breaststroke swimmers. The mean ages and best times for a 50-m breaststroke were, respectively, (recreational: 16.9±1.6 y; 49.55±3.38 s; competitive: 16.2±1.5 y; 33.85±1.96 s). Each swimmer was required to swim 2×25-m breaststroke at two different paces (slow and sprint) while being videotaped by two underwater cameras (frontal and lateral views). At the same given speed, recreational swimmers used no glide phase which increased the relative contribution of their recovery and propulsive phases. This was mainly caused by the superposition of their leg extension and the second part of their arm recovery, indicating a technique with no glide time between the arm recovery and the leg extension. In terms of phase duration, the recreational swimmers spent more time in arm recovery and in propulsive phases. Furthermore, it was observed that for a comparable increase of swimming speed (recreational: 23.3%, competitive: 22.6%), competitors switched from a glide to an overlapped coordination while recreational swimmers adopted an overlapped technique whatever the swimming speed. As a result, the relative time spent in propulsive phases did not change in the recreational group, but increased by 27.2% in the competitive one. In a swimming developmental program, particular emphasis should be put on arm-leg coordination drills, when considering the breaststroke.